DCE-MRI of the breast in a stand-alone setting outside a complementary strategy: results of the TK-study - Kaiser, Clemens G.; Krammer, Julia; Wasser, Klaus; Schönberg, Stefan (European radiology, 2015)
Objectives: To evaluate the accuracy of MRI of the breast (DCE-MRI) in a stand-alone setting with extended indications. Materials and methods: According to the inclusion criteria, breast specialists were invited to refer patients to our institution for DCE-MRI. Depending on the MR findings, patients received either a follow-up or biopsy. Between 04/2006 and 12/2011 a consecutive total of 1,488 women were prospectively examined. Results: Of 1,488 included patients, 393 patients were lost to follow-up, 1,095 patients were evaluated. 124 patients were diagnosed with malignancy by DCE-MRI (76 TP, 48 FP, 971 TN, 0 FN cases). Positive cases were confirmed by histology, negative cases by MR follow-ups or patient questionnaires over the next 5 years in 1,737 cases (sensitivity 100 %; specificity 95.2 %; PPV 61.3 %; NPV 100 %; accuracy 95.5 %). For invasive cancers only (DCIS excluded), the results were 63 TP; 27 FP; 971 TP and 0 FN (sensitivity 100 %; specificity 97.2 %; PPV 70 %; NPV 100 %; accuracy 97.5 %). Conclusion: The DCE-MRI indications tested imply that negative results in DCE-MRI reliably exclude cancer. The results were achieved in a stand-alone setting (single modality diagnosis). However, these results are strongly dependent on reader experience and adequate technical standards as prerequisites for optimal diagnoses. Key Points: DCE-MRI of the breast has a high accuracy in finding breast cancer. The set of indications for DCE-MRI of the breast is still very limited. DCE-MRI can achieve a high accuracy in a ‘screening-like’ setting. Accuracy of breast DCE-MRI is strongly dependent on technique and reader experience. A negative DCE-MRI effectively excludes cancer.